The Tahlilan Culture of Darupono Village That is Still Preserved by the Community - Muhammad Zubdanil Fanni Tafii; Mohammad Lubabul Fawaid; Muhammad Ridwan Abdullah; Salma Nuriya Kusuma; Oktaviyanti Oktaviyanti; Sayyidatu Uswatun Hasanah; Suwahono Suwahono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Tahlilan is an Islamic tradition that is carried out as a form of communal prayer to pray for the souls of the deceased. This culture is very strong in various regions in Indonesia, including in Darupono Village. This article aims to analyze how the tahlilan culture is still preserved by the people of Darupono Village amidst social change and modernization. This study uses a qualitative method with an ethnographic approach, where data is collected through observation, in-depth interviews, and documentation. The results of the study show that tahlilan in Darupono Village not only functions as a religious ritual, but also as a means of strengthening ties and maintaining local cultural identity.